Effect of video learning multimedia toward health belief model of self breast examination - Fatmah Afrianty Gobel; Nurfitriani Nurfitriani; Samsualam Samsualam (CORE JOURNAL, 2020)
Breast cancer is the most commonly diagnosed cancer and the second leading cause of death from cancer for women. The prevalence of cancer in Indonesia is 1.4 per 1000 inhabitants or about 330,000 people. VLM (Video Learning Multimedia) is a learning tool or medium using video or mobile display, using a combination of text, graphics, sound, video and animation. Aim of study was measure effect of VLM toward self breast examination behavior. This type of research is quantitative research with a population of 135. As for the number of samples in this study as many as 60 respondents, which are divided into two groups namely, intervention group and control group. We used paired sample test with 95% confidence level, obtained p-value= 0.001, meaning there was a difference in attitude before and after being educated on breast check behavior (SADARI) in the control group. Factors that facilitate the change in a person's behavior, consisting of knowledge, attitudes, and cultural values.  It is expected that it will be useful for mothers in Buakana Village rappocini sub-district and society especially women who are more at high risk of breast cancer to not only study but perform breast examination themselves (SADARI) as an early detection of breast cancer